A process for producing polylactic acid(PLA)-cellulose nanocomposite. - Harun, Jalaludin; Md. Tahir, Paridah; Jonoobi, Mehdi; Osman Al-Edrus, Syeed SaifulAzry (2010)

(untitled)
The present invention relates to a process for producing polylactic acid (PLA)- cellulose nanocomposite. The PLA-cellulose nanocomposite includes polymer matrix and cellulose nanofibers. The cellulose nanofibers having concentration of 1wt% to 5wt%. The cellulose nanofibers (CNF) are obtained from kenaf pulp. The cellulose nanofibers from kenaf pulp are reinforcing phase in PLA matrix. The cellulose nanofibers are kenaf nanofibers. The PLA-cellulose nanocomposite is produced using a two-step process: (i) preparing a pre-mixture of crushed CNF-films with PLA followed by (ii) compounding and extruding process.